Minimization of flickering of impulse modulated illumination in projection systems on microdisplays of reflective type - D. V. Chistobaev; E. A. Krasnobaev; A. A. Stepanov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The effect of pulsed LED light sources, widely used for illumination in projection optical indicator systems on perception of human vision, is analyzed. An analysis of the impulse signal of reflectors illumination has been carried out. Modeling and analysis of flickerings of a binary pulse-code modulated signal has been performed. Recommendations for reducing of visible flickering of the LED backlight up to the minimum level have been given.